Determinan Audit Delay pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia - Azkia, Saufa; Budiantoro , Risanda Alirasta (Yayasan Pendidikan Mitra Mandiri Aceh(YPMMA), 2025)
Auditing financial statements is an integral part of the company's financial reporting process. This study aims to examine the influence of company size, company age, and profitability on audit delays in manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2021–2024 period. In addition, this study also analyzes the role of regulation as a moderation variable that can strengthen or weaken the relationship between variables. Signal theory is used as a theoretical foundation in explaining the relationship between company characteristics and the timeliness of audit reporting. This study uses a quantitative approach with a panel data regression analysis method. The sample consisted of 30 manufacturing companies selected through purposive sampling techniques during the observation period. The results showed that company size did not have a significant effect on audit delays, while company age and profitability had a significant negative effect. This means that companies that are longer established and more profitable tend to complete the audit process faster. In terms of moderation, regulations do not significantly moderate the relationship between the size and age of companies and audit delays. However, regulation has been shown to significantly moderate the effect of profitability on audit delays, with a direction of moderation that weakens the negative relationship. These findings suggest that while profitability drives the acceleration of audits, regulatory pressures still limit the flexibility of reporting times.